Journalism Policy across the Commonwealth: Partial Answers to Public Problems. Issue 3 (16th March 2021) - Meese, James
Abstract: Governments and policymakers are considering intervening in the relationship between major tech companies and the news media industry and holding various inquiries and reviews to canvass reform options. This article provides a comparative study of Australia, Canada and the United Kingdom, some of the earliest countries in the world to engage in these policy processes. The study reveals that these media systems have devised similar regulatory tools and their approach aligns with a more disaggregated set of reforms occurring across Europe. While these reform agendas often draw on valuable concepts from media policy, they also awkwardly translate frameworks and introduce already questionable regulatory approaches to the platform environment. The most notable is the ongoing focus on stakeholders instead of the wider public interest. I end the paper by arguing the long-term sustainability of journalism need to be decoupled from attempts to limit platform power. I outline a more targeted regulatory response focussed on antitrust and privacy and note that journalism will receive downstream benefits from these efforts. The approach challenges the core issues associated with platform dominance and stands in contrast to current reform proposals, which threaten to hamper much needed institutional transformation across the journalism sector